Influence of extraction conditions on structural and functional characteristics of black cumin protein concentrates and ACE-inhibition in their hydrolyzates - (:unkn) unknown (SPRINGER, 2019)
Cold press oils are value-added food ingredients that are increasingly produced. Due to the removal of oil, protein content in cold press deoiled meals substantially increase. Here, we made an attempt to manufacture protein concentrates from cold press meals of black cumin and studied the influence of aqueous (alkali extraction-isoelectric precipitation, AE-IP) and organic (n-hexane) extraction conditions on the structure and functionality of these concentrates. To determine the basic structural attributes, SDS-PAGE and 2D-electrophoresis, DSC, rheological and FT-IR analysis were utilized. Black cumin proteins contained both alpha- and beta-secondary structural elements, and the proteins were potentially glycosylated. This in turn affected their gel-like behavior prior to heating. The presence of a number of high pI proteins was also detected via 2D-electrophoresis. Functional characteristics of the concentrates were investigated based on solubility, water and oil holding capacities, and dynamic surface tension analysis. Deoiled meals contained 22.3% oil, which was only slightly affected by aqueous extraction. Protein content in the meals was approx. 26.5% which increased to 57.7 and 65.8%, after aqueous (AE-IP) extraction and both aqueous (AE-IP) and hexane extraction, respectively. Solubility, WHC, OHC were found to be improved by hexane extraction. Based on DSC analysis, presence of black cumin oil in the concentrates enhanced the thermal stability of the proteins, while black cumin proteins demonstrated considerable surface activity at the air-water interface. Finally upon enyzmatic proteolysis, protein hydrolyzates demonstrated slight angiotensin-converting enzyme (ACE)-inhibitory activity. Based on the current findings, deoiled black cumin meals represent a viable source of biologically and technically functional proteins.
Keywords: Cold press meals; Protein concentrates; Black cumin; Protein functionality; ACE-inhibition; ISOELECTRIC PRECIPITATION; PEA; PERFORMANCE; PRODUCTS; CHICKPEA; ISOLATE; LENTIL; MEAL; L.; PH